From National to Local: Media-citizen Councils as Independent Co-regulation at the Community Level - Mateo, Mia; Mariano, Gary; Mateo, Janvic; Sebellino, Ariel (Department of Communications, Universitas Islam Indonesia, 2024)
Following Miranda & Camponez (2019), media regulation or accountability in the Philippines has evolved from mandated/professional in 1965, to mandated/shared, to voluntary/professional in the late 1980s, and to voluntary/shared in the early 2000s. Today, the Philippine Press Institute is leading a multisectoral effort to establish community-based media-citizen councils outside Manila, signifying a shift from the national to local. Applying key informant interviews to collect the empirical data, this study has interviewed the Media-Citizen Council officers and members through face-to-face interviews or Zoom meetings. This study found that these media-citizen councils are local in nature. They were established in the different regions of the country to address media-related issues and complaints within their media companies and communities in their specific regions. These councils are also expanding their scope from traditional newspapers to include the broadcast and the emerging social media, and extending membership to locally-relevant stakeholders.